Cellular microporous in-situ phase separation polymer uv liquid membrane and preparation method thereof

CN122832609BActive Publication Date: 2026-10-30UNIV OF SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611327325.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30
Estimated Expiration
2046-08-31

AI Technical Summary

Technical Problem

此类工艺施工繁琐,且层间界面结合力弱,长期使用易出现剥离脱落,稳定性不足

Benefits of technology

1、本发明构建的单组分介稳态微乳液体系,大部分组分采用食品级或生物相容性无毒材料,施工铺展及成膜的过程无刺激性或有害物质释放,可直接施用于植物表面,对环境与生物体友好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122832609B_ABST
    Figure CN122832609B_ABST
Patent Text Reader

Abstract

The application discloses a kind of cellular microporous in-situ phase separation high molecular ultraviolet liquid membrane and preparation method, belong to functional membrane material and multilayer coating technical field.Liquid membrane is single-component metastable microemulsion system before being applied, consisting of hydrophilic phase, hydrophobic phase, inducing agent.Inducing agent volatilization triggers system instability after being applied, and hydrophilic and hydrophobic phases occur in-situ phase separation, and hydrophobic phase floats to form upper membrane, and hydrophilic phase sinks to form lower membrane;Inducing agent is driven surface rheology by marangoni effect, and regular cellular microporous structure is spontaneously formed in upper membrane.Upper membrane realizes 300~380nm ultraviolet light high-efficiency reflection by cellular microporous structure and nanometer silicon dioxide, and lower membrane forms three-dimensional porous network structure to wrap bird repellent active component, and forms two-stage slow-release structure with the cellular microporous structure of upper layer.The application can construct double-layer functional membrane by one-step construction, has ultraviolet light warning and long-acting bird repellent function, and is suitable for being applied to the surface of various substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional membrane materials and multilayer coating technology, specifically relating to a honeycomb microporous in-situ phase-separated polymer ultraviolet liquid membrane and its preparation method, and particularly to a green and environmentally friendly liquid membrane based on the Marangoni effect and self-assembly mechanism, which has both ultraviolet light reflection and long-term sustained-release functions. Background Technology

[0002] With the development of functional surface engineering, smart coatings and biomimetic materials, liquid film materials with functions such as optical control, environmental protection and release of active substances have gradually become a research hotspot. They have the characteristics of convenient construction, applicability to complex substrates and easy large-area coverage, and have broad application prospects in building facilities, transportation facilities, agricultural facilities and ecological protection.

[0003] In existing technologies, coatings that combine ultraviolet reflection and slow-release functions are mostly prepared using prefabricated multilayer film structures or layer-by-layer composite processes. For example, Chinese invention patent application CN114479693A discloses an ultraviolet reflection optical film, which requires the construction of a multilayer optical structure to achieve its function; Chinese invention patent application CN105833732A discloses a hydrophilic antifouling separation membrane, which forms functional layers layer by layer through surface grafting. Such processes are cumbersome to construct, and the interlayer interface bonding is weak, making them prone to peeling and detachment after long-term use, resulting in insufficient stability.

[0004] In the field of bird-repellent protective coatings, existing products mostly use conventional resins as a matrix mixed with bird-repellent active components, which generally suffer from the problems of rapid volatilization of bird-repellent active components and short protective duration. Moreover, some systems use irritating organic solvents, causing environmental pollution during construction and film formation. In addition, existing functional coatings are unable to spontaneously form regular micro-nano honeycomb array structures during film formation, cannot improve ultraviolet reflection performance through structural optics effects, and cannot regulate the release rate of bird-repellent active components by means of micro-nano container structures. They cannot simultaneously meet the comprehensive requirements of physical optical warning, long-term chemical slow release, and environmentally friendly construction process.

[0005] Therefore, developing a liquid membrane that is stable in storage, environmentally friendly in construction, and can spontaneously construct a double-layer functional structure and a honeycomb microporous array through its own volatilization process after application is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a honeycomb microporous in-situ phase-separated polymer ultraviolet liquid membrane and its preparation method, which realizes the one-step construction of an integrated double-layer functional membrane, and has the characteristics of high-efficiency ultraviolet light reflection, long-lasting bird-repellent active component sustained release, and environmentally friendly construction and film formation process.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a honeycomb microporous in-situ phase-separated polymer ultraviolet liquid membrane, which is a single-component metastable microemulsion system before coating, consisting of a hydrophilic phase, a hydrophobic phase, and an inducing agent; the hydrophilic phase and the hydrophobic phase exist in the system in a micro-dispersion state.

[0008] The hydrophilic phase, by weight, comprises: 60-100 parts propylene glycol, 30-50 parts vegetable glycerin, 1-3 parts polyglutamic acid, 1-2 parts sodium hyaluronate, 2-5 parts chitosan or hydroxyethyl cellulose, 3-6 parts trehalose, 1-3 parts allantoin, and 100-160 parts bird-repelling active ingredients; the bird-repelling active ingredients, by weight, comprise: 40-60 parts cinnamon extract, 50-70 parts capsaicin or capsaicin, and 10-30 parts methyl anthranilate.

[0009] The hydrophobic phase comprises, by weight, 80-120 parts of polydimethylsiloxane, 40-60 parts of polydimethylsiloxane alcohol, 30-50 parts of inorganic silicate or inorganic silicone resin, 50-70 parts of modified nano-silica sol with a particle size of 150-200 nm, and 20-40 parts of natural palm wax microemulsion or natural beeswax.

[0010] The inducer is a green volatile driving medium and a honeycomb structure inducer, which includes, by weight: 30-60 parts of anhydrous ethanol, 20-60 parts of deionized water, 3-8 parts of polyether-modified silicone oil, and 2-5 parts of modified tea saponin or soybean lecithin; wherein, anhydrous ethanol and soybean lecithin are preferably food grade, so that all components are made of non-toxic and harmless food grade or biocompatible materials.

[0011] After the liquid film is applied to the substrate surface, the inducing agent gradually evaporates, causing instability in the metastable microemulsion system. Under the influence of differences in interfacial tension and surface free energy, the hydrophilic and hydrophobic phases undergo in-situ phase separation. The hydrophobic phase migrates towards the air interface to form the upper film, while the hydrophilic phase migrates towards the substrate interface to form the lower film. During the evaporation and film formation process, the inducing agent drives surface rheology and micro-separation of the liquid phase through the Marangoni effect, spontaneously forming a regular honeycomb microporous structure on the surface and inside of the upper film. The upper film, through interfacial reflection, structural scattering, and multiple scattering caused by the honeycomb microporous structure, interacts with nano-carbon dioxide... The scattering effect of silicon particles synergistically enhances the reflectivity of ultraviolet light in the 300–380 nm wavelength band. A continuous three-dimensional porous network structure is formed inside the lower membrane, encapsulating the bird-repelling active component. The bird-repelling active component first migrates slowly within the three-dimensional porous network structure and then diffuses further towards the upper membrane. The honeycomb microporous structure of the upper membrane regulates the migration and volatilization process of the bird-repelling active component, allowing it to be gradually released to the outside through the honeycomb microporous structure. This forms a two-stage slow-release structure composed of the three-dimensional porous network structure of the lower membrane and the honeycomb microporous structure of the upper membrane.

[0012] Furthermore, the pore size of the honeycomb microporous structure is 500nm~5μm, and the pore depth is 200nm~2μm.

[0013] Furthermore, the upper membrane accounts for 30% to 70% of the total thickness of the liquid membrane, and the lower membrane accounts for 30% to 70% of the total thickness of the liquid membrane.

[0014] Furthermore, the inorganic nanoparticles in the upper film are uniformly dispersed in the silicon-based continuous phase and the walls of the honeycomb micropores, forming micro-nano scale surface undulations and periodic honeycomb micropore structures.

[0015] Furthermore, the hydrophilic polymer network in the lower membrane is a continuous three-dimensional porous network structure, with the bird-repelling active components dispersed within the network. Long-term slow release is achieved through a two-stage sustained-release structure formed by the honeycomb microporous structure of the upper membrane and the three-dimensional porous network structure of the lower membrane. Moreover, the upper and lower membranes are formed in situ as an integral structure, and the honeycomb microporous structure on the surface does not disrupt the continuity of the bilayer phase separation interface, resulting in strong interlayer bonding and no risk of peeling.

[0016] The present invention also provides a method for preparing the above-mentioned honeycomb microporous in-situ phase-separated polymer ultraviolet liquid film, comprising the following steps: S1. Preparation of the hydrophilic phase: Polyglutamic acid, sodium hyaluronate, chitosan or hydroxyethyl cellulose are added to a first dissolving medium (such as deionized water or other liquids that can dissolve the above substances) and dispersed and fully swollen. Trehalose, allantoin, propylene glycol and vegetable glycerin are added to form a mixture. Bird-repelling active components (cinnamon extract, capsaicin or capsaicin and methyl anthranilate) are dissolved in a second dissolving medium (such as anhydrous ethanol or other liquids that can dissolve the above substances). The mixture is added and sheared to obtain the hydrophilic phase.

[0017] S2. Preparation of hydrophobic phase: Polydimethylsiloxane, polydimethylsiloxane alcohol, inorganic silicate or inorganic silicone resin, modified nano silica sol and natural palm wax microemulsion or natural beeswax are mixed and ultrasonically dispersed to obtain a hydrophobic phase.

[0018] S3. Emulsification and homogenization: The hydrophilic phase and the hydrophobic phase are emulsified under high shear, and an inducing agent composed of deionized water, anhydrous ethanol, polyether-modified silicone oil and modified tea saponin or soybean lecithin is added. After high-speed homogenization, a single-component metastable microemulsion system is obtained.

[0019] Furthermore, in step S1, the dispersion and swelling temperature is 20–40℃, and the shear dispersion speed is 800–1000 rpm; in step S2, the ultrasonic dispersion time is 20–40 min; in step S3, the high-shear emulsification speed is 1200–1500 rpm, the high-speed homogenization speed is 2000–3000 rpm, the homogenization time is 2–5 min, and the system temperature is controlled at 18–20℃ during the preparation process.

[0020] Compared with the prior art, the present invention has the following advantages: 1. The single-component metastable microemulsion system constructed in this invention uses food-grade or biocompatible non-toxic materials for most of its components. The process of construction, spreading and film formation does not release any irritating or harmful substances and can be directly applied to the plant surface, which is environmentally friendly and beneficial to organisms.

[0021] 2. This invention breaks through the limitations of traditional multilayer film layer-by-layer composite process. Relying on the system instability induced by solvent evaporation, it forms a film in situ in one step, so that the hydrophilic and hydrophobic phases spontaneously separate in situ, and simultaneously form an upper hydrophobic functional layer and a lower hydrophilic adhesive layer. The double-layer structure is formed in situ as a whole, the interface is continuous and there is no risk of peeling. The construction process is simple and it is suitable for surface treatment of large-area complex substrates.

[0022] 3. This invention utilizes the interfacial tension gradient induced by an inducing agent to drive surface rheology through the Marangoni effect, spontaneously forming a highly ordered honeycomb microporous structure in the upper film. The interfacial reflection, structural scattering, and multiple scattering effects caused by the periodic honeycomb microporous structure, in synergy with the scattering effect of nano-silica particles, significantly enhance the reflection efficiency of ultraviolet light in the 300~380nm band, resulting in outstanding physical optical warning effects.

[0023] 4. This invention uses the honeycomb microporous structure of the upper membrane as a secondary sustained-release mechanism for the bird-repelling active component, which together with the primary sustained-release mechanism of the continuous three-dimensional porous network structure of the lower membrane to construct a two-stage sustained-release structure. This effectively reduces the diffusion rate and volatilization loss of the bird-repelling active component in the lower membrane. The two-stage sustained-release structure differs from the traditional single-matrix diffusion mode and can extend the continuous release period of the bird-repelling active component to more than 40 days, resulting in excellent long-term protective performance.

[0024] 5. The liquid film of this invention can be stably formed on the surface of various substrates such as glass, metal, concrete, polymer and plant leaves. It has good adhesion performance and stable function, and can be widely used in bird protection scenarios such as building exterior walls, power transmission and distribution towers, agricultural greenhouses, airport facilities and agricultural and forestry plants. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the preparation process of the liquid membrane of the present invention.

[0026] Figure 2This is a schematic diagram of the double-layer structure of the liquid film after film formation and the substrate of the present invention.

[0027] Figure 3 This is a schematic diagram of the in-situ phase separation and honeycomb microporous structure formation mechanism of the present invention.

[0028] Figure 4 This is a schematic diagram of the dual-channel long-acting sustained-release mechanism of the present invention. Detailed Implementation

[0029] The present invention will be further described below.

[0030] Example 1 (Optimal Example): This example describes the preparation of a honeycomb microporous in-situ phase-separated polymer ultraviolet liquid membrane. The specific steps are as follows: S1. Preparation of the hydrophilic phase: At 25℃, 2 parts polyglutamic acid, 1.5 parts sodium hyaluronate, and 3 parts chitosan were added to 30 parts deionized water and dispersed by shearing at 900 rpm for 30 min to allow for full swelling. Subsequently, 4.5 parts trehalose, 2 parts allantoin, 80 parts propylene glycol, and 40 parts vegetable glycerin were added sequentially and stirred until homogeneous. Separately, 50 parts cinnamon extract, 60 parts capsaicin, and 20 parts methyl anthranilate were dissolved in 20 parts food-grade anhydrous ethanol and poured into the above system. The mixture was dispersed by shearing at 900 rpm for 15 min to obtain the hydrophilic phase. The main active ingredient of the cinnamon extract, calculated as cinnamaldehyde, had a mass fraction ≥95%.

[0031] S2. Preparation of hydrophobic phase: 100 parts of polydimethylsiloxane, 50 parts of polydimethylsiloxane alcohol, 40 parts of inorganic silicate, 60 parts of modified nano silica sol (particle size 180nm) and 30 parts of natural palm wax microemulsion were mixed and ultrasonically dispersed at 25℃ for 30min to obtain a uniformly dispersed hydrophobic phase.

[0032] S3. Emulsification and homogenization: The hydrophilic phase obtained in step S1 is mixed with the hydrophobic phase obtained in step S2, and emulsified at high shear at 1300 rpm for 5 min. After completion, a driving induction system consisting of 20 parts deionized water, 30 parts food-grade anhydrous ethanol, 5 parts polyether modified silicone oil and 3.5 parts modified tea saponin is added. The system temperature is controlled at 19℃, and the system is homogenized at high speed at 2500 rpm for 3 min to obtain a single-component metastable microemulsion system.

[0033] The liquid film of this embodiment was sprayed onto the surface of plant leaves for performance testing. The evaporation of ethanol and water drove the system to become unstable and undergo in-situ phase separation. The test results are shown in Table 1 below: Table 1: Performance test results of liquid film sprayed on plant leaf surfaces

[0034] Characterization revealed that the lower membrane is formed by a hydrophilic polymer network of hydrophilic phase, which adheres firmly to the plant epidermis and exhibits a three-dimensional porous network structure. The upper membrane is formed by the migration of hydrophobic phase to the air interface. Driven by the Marangoni effect of polyether-modified silicone oil and tea saponin, a honeycomb microporous structure is spontaneously formed on the surface and inside, with a pore size ranging from 500 nm to 5 μm and a pore depth ranging from 200 nm to 2 μm. The honeycomb microporous structure prepared in this embodiment has an average pore size of 1.2 μm and an average pore depth of 600 nm.

[0035] Example 2: The specific steps are as follows: S1. Preparation of the hydrophilic phase: At 20℃, 1 part polyglutamic acid, 1 part sodium hyaluronate, and 2 parts chitosan were added to 25 parts deionized water and dispersed by shearing at 800 rpm for 30 min to allow for full swelling. Subsequently, 3 parts trehalose, 1 part allantoin, 60 parts propylene glycol, and 30 parts vegetable glycerin were added sequentially and stirred until homogeneous. Separately, 40 parts cinnamon extract, 50 parts capsaicin, and 10 parts methyl anthranilate were dissolved in 15 parts food-grade anhydrous ethanol and poured into the above system. The mixture was dispersed by shearing at 800 rpm for 15 min to obtain the hydrophilic phase.

[0036] S2. Preparation of hydrophobic phase: 80 parts of polydimethylsiloxane, 40 parts of polydimethylsiloxane alcohol, 30 parts of inorganic silicate, 50 parts of modified nano silica sol (particle size 150nm) and 20 parts of natural palm wax microemulsion were mixed and ultrasonically dispersed at 20℃ for 20min to obtain a uniformly dispersed hydrophobic phase.

[0037] S3. Emulsification and homogenization: The hydrophilic phase obtained in step S1 and the hydrophobic phase obtained in step S2 are mixed at a mass ratio of 1:0.8 and emulsified at 1200 rpm for 5 min under high shear. After completion, the mixture is added to a driving induction system consisting of 40 parts deionized water, 40 parts food-grade anhydrous ethanol, 3 parts polyether modified silicone oil and 2 parts modified tea saponin. The system temperature is controlled at 18℃ and homogenized at 2000 rpm for 2 min to obtain a single-component metastable microemulsion system.

[0038] Example 3: The specific steps are as follows: S1. Preparation of the hydrophilic phase: At 40℃, 3 parts polyglutamic acid, 2 parts sodium hyaluronate, and 5 parts hydroxyethyl cellulose were added to 35 parts deionized water and dispersed by shearing at 1000 rpm for 40 min to allow for full swelling. Subsequently, 6 parts trehalose, 3 parts allantoin, 100 parts propylene glycol, and 50 parts vegetable glycerin were added sequentially and stirred until homogeneous. Separately, 60 parts cinnamon extract, 70 parts capsaicin, and 30 parts methyl anthranilate were dissolved in 25 parts food-grade anhydrous ethanol and poured into the above system. The mixture was dispersed by shearing at 1000 rpm for 20 min to obtain the hydrophilic phase.

[0039] S2. Preparation of hydrophobic phase: 120 parts of polydimethylsiloxane, 60 parts of polydimethylsiloxane alcohol, 50 parts of inorganic silicone resin, 70 parts of modified nano silica sol (particle size 200nm) and 40 parts of natural beeswax were mixed and ultrasonically dispersed at 35℃ for 40min to obtain a uniformly dispersed hydrophobic phase.

[0040] S3. Emulsification and homogenization: The hydrophilic phase obtained in step S1 and the hydrophobic phase obtained in step S2 are mixed at a mass ratio of 1:1.2 and emulsified at 1500 rpm for 5 min under high shear. After completion, the mixture is added to a driving induction system consisting of 60 parts deionized water, 60 parts food-grade anhydrous ethanol, 8 parts polyether-modified silicone oil and 5 parts food-grade soybean lecithin. The system temperature is controlled at 20℃ and homogenized at 3000 rpm for 5 min to obtain a single-component metastable microemulsion system.

[0041] Performance verification: 1. To verify the effect of the mass ratio of hydrophilic phase to hydrophobic phase on the performance of liquid membrane, the preparation method was the same as in Example 1, only the mass ratio of hydrophilic phase to hydrophobic phase was adjusted, while the other components and process conditions remained the same. Three groups of experiments were set up: Group A hydrophilic phase: hydrophobic phase = 1:0.8, Group B hydrophilic phase: hydrophobic phase = 1:1, and Group C hydrophilic phase: hydrophobic phase = 1:1.2.

[0042] Each group of liquid films was sprayed onto the surface of a standard quartz glass sheet (a type of glass substrate) with a thickness of approximately 120 μm. The films were then allowed to cure naturally at 25°C and 50% relative humidity. The test results are shown in Table 2 below. Table 2: Performance test results of liquid film sprayed onto standard quartz glass sheets

[0043] The determination of the continuous release time of the above-mentioned active components was based on the effectiveness of bird behavior-based repellency as the criterion. Specifically, the detection and judgment method was as follows: Equal amounts of bird bait were placed in a standard test area. The number of landings, dwell time, and feeding rate of birds in the experimental group and the blank control group were continuously recorded using a monitoring system. The overall repellency rate (i.e., the sum of all bird repellency rates) was calculated. A "comprehensive repellency rate maintained above 85%" was used as the criterion for determining whether the coating was in continuous release time. When, over time, the volatilization of the active components weakened, causing the overall repellency rate to drop below 85% for the first time, it was determined that the "continuous release time of the active components had ended" for that group of samples. The ultraviolet reflectance was the average reflectance of the liquid film sample in the wavelength range of 300–380 nm, calculated based on the reflectance spectrum within this band.

[0044] Test results show that different ratios reflect the changes in the thickness ratio of the honeycomb microporous structure of the upper membrane to the three-dimensional porous network structure of the lower membrane caused by changes in the hydrophilic-hydrophobic phase mass ratio, thus regulating the release rate of the active component. With increasing hydrophobic phase ratio, the UV reflectance of the upper membrane initially increases and then stabilizes; while with increasing hydrophilic phase ratio, the sustained-release time of the bird-repellent active component in the lower membrane also initially increases and then decreases. When the mass ratio of hydrophilic to hydrophobic phase is 1:1, the liquid membrane exhibits both high UV reflectance and good sustained-release performance, resulting in the optimal overall performance.

[0045] 2. To verify the film-forming performance of the liquid film on different substrates, liquid films were prepared according to the method in Example 1 and sprayed onto glass plates, 304 stainless steel plates, galvanized steel plates, concrete substrates, polycarbonate plates, and plant leaf surfaces, respectively. Each substrate was only wiped to remove surface dust; no special treatment was performed. To ensure consistency of the test standards, all tests with different formulations and substrates were conducted under the same environmental conditions (ambient temperature 25±2℃, relative humidity 50±5%, spray thickness 100~120μm) with continuous field / simulated monitoring and statistical analysis. The test standards were unified, and the data had strict cross-sectional comparability. The test results are shown in Table 3 below: Table 3: Test results of film-forming performance of liquid films on different substrates

[0046] The above tests on different substrates reflect the actual impact of the microstructure and interfacial porosity of different substrate surfaces (such as the adsorption and anchoring of the membrane on porous concrete surfaces prolonging the odor release, while the membrane time of plant leaves is relatively short due to surface metabolic activity) on the release cycle of active components, which is consistent with the actual laws of materials on different application interfaces. The test results show that the liquid membrane of the present invention can be stably formed on the surface of various types of substrates, with good adhesion performance and functional stability, and excellent substrate adaptability.

[0047] 3. To verify the repellency effect and long-term protective performance of the liquid membrane on birds, the liquid membrane was prepared according to the method in Example 1, and four common birds, namely magpie, wild duck, sparrow and pigeon, were selected as test subjects.

[0048] A simulated field test area was set up, and the liquid film of this invention was sprayed onto the surfaces of four substrates: agricultural facility netting, fruit tree leaves, metal power towers, and concrete building exterior walls. The coating thickness was 100-120 μm, and the coating was allowed to cure naturally for 20 minutes to form a double-layer functional film. The same substrate without coating was used as a blank control group. The landing frequency, average dwell time, and feeding rate of the four bird species in each application scenario were monitored and statistically analyzed over 30 days. Furthermore, within the same statistical period, the data obtained from the four application scenarios were summarized according to the same statistical caliber. The results were used to evaluate the comprehensive repellency effect of the liquid film on the four bird species, as shown in Table 4 below: Table 4: Results of comprehensive repulsion tests of liquid films on four bird species on different substrate surfaces

[0049] Using the same statistical range and calculation method as Table 4 above, continuous monitoring was conducted until day 45. Due to the two-stage sustained-release structure jointly constructed by the honeycomb microporous structure of the upper membrane and the three-dimensional porous network structure inside the lower membrane, the bird-repelling active components were released in a two-stage sustained-release manner. The overall repellency rate of the four bird species in the experimental group (i.e., the repellency rate calculated after summing the four bird species) remained above 89.5%, indicating that the liquid membrane of the present invention has excellent and long-lasting repellency and protection effect against common birds in complex outdoor environments.

Claims

1. A honeycomb microporous in-situ phase-separated polymer ultraviolet liquid membrane, characterized in that, Before application, the liquid film is a single-component metastable microemulsion system composed of a hydrophilic phase, a hydrophobic phase, and an inducer; the hydrophilic and hydrophobic phases exist in the system in a micro-dispersion state. The hydrophilic phase comprises, by weight, 60-100 parts propylene glycol, 30-50 parts vegetable glycerin, 1-3 parts polyglutamic acid, 1-2 parts sodium hyaluronate, 2-5 parts chitosan or hydroxyethyl cellulose, 3-6 parts trehalose, 1-3 parts allantoin, and 100-160 parts bird-repelling active ingredients. The hydrophobic phase comprises, by weight, 80-120 parts of polydimethylsiloxane, 40-60 parts of polydimethylsiloxane alcohol, 30-50 parts of inorganic silicate or inorganic silicone resin, 50-70 parts of modified nano-silica sol with a particle size of 150-200 nm, and 20-40 parts of natural palm wax microemulsion or natural beeswax. The inducing agent comprises, by weight: 30-60 parts anhydrous ethanol, 20-60 parts deionized water, 3-8 parts polyether-modified silicone oil, and 2-5 parts modified tea saponin or soybean lecithin. When the liquid film is applied to the substrate surface, the volatilization of the inducer causes the system to become unstable. Under the influence of the difference in interfacial tension and surface free energy, the hydrophilic and hydrophobic phases undergo in-situ phase separation. The hydrophobic phase migrates towards the air interface to form the upper film, while the hydrophilic phase migrates towards the substrate interface to form the lower film. During the film formation process, the inducer drives surface rheology and liquid phase micro-separation through the Marangoni effect, spontaneously forming a honeycomb microporous structure on and inside the upper film. A three-dimensional porous network structure is formed inside the lower film, encapsulating the bird-repelling active component. The bird-repelling active component first migrates slowly within the three-dimensional porous network structure and then diffuses further towards the upper film. The honeycomb microporous structure of the upper film regulates the migration and volatilization process of the bird-repelling active component, allowing it to be gradually released to the outside through the honeycomb microporous structure, thus forming a two-stage slow-release structure composed of the three-dimensional porous network structure of the lower film and the honeycomb microporous structure of the upper film.

2. The polymer ultraviolet liquid film according to claim 1, characterized in that, The bird-repelling active ingredients, by weight, include: 40-60 parts of cinnamon extract, 50-70 parts of capsaicin or capsaicin, and 10-30 parts of methyl anthranilate.

3. The polymeric ultraviolet liquid film according to claim 1, characterized in that, The pore size of the honeycomb microporous structure is 500nm~5μm, and the pore depth is 200nm~2μm.

4. The polymeric ultraviolet liquid film according to claim 1, characterized in that, The upper membrane achieves the reflection of ultraviolet light in the 300–380 nm wavelength band through the synergistic effect of interface reflection and structural scattering generated by the honeycomb microporous structure and the scattering effect of nanoparticles.

5. The polymer ultraviolet liquid film according to claim 1, characterized in that, The upper membrane accounts for 30% to 70% of the total thickness of the liquid membrane, and the lower membrane accounts for 30% to 70% of the total thickness of the liquid membrane.

6. The polymer ultraviolet liquid film according to claim 1, characterized in that, The hydrophilic polymer network in the lower membrane is a continuous three-dimensional porous network structure, and the bird-repelling active components are dispersed inside the hydrophilic polymer network.

7. A method for preparing the polymeric ultraviolet liquid film according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Preparation of the hydrophilic phase: Polyglutamic acid, sodium hyaluronate, chitosan or hydroxyethyl cellulose are added to the first dissolving medium, dispersed and fully swollen, and then trehalose, allantoin, propylene glycol and vegetable glycerin are added to form a mixture; the bird-repelling active component is dissolved in the second dissolving medium, and the above mixture is added and sheared to obtain the hydrophilic phase; S2. Preparation of hydrophobic phase: Polydimethylsiloxane, polydimethylsiloxane alcohol, inorganic silicate or inorganic silicone resin, modified nano silica sol and natural palm wax microemulsion or natural beeswax are mixed and ultrasonically dispersed to obtain a hydrophobic phase; S3. Emulsification and homogenization: The hydrophilic phase and the hydrophobic phase are emulsified under high shear, and an inducing agent composed of deionized water, anhydrous ethanol, polyether-modified silicone oil and modified tea saponin or soybean lecithin is added. After high-speed homogenization, a single-component metastable microemulsion system is obtained.

8. The method according to claim 7, characterized in that, In step S1, the dispersion and swelling temperature is 20–40℃, and the shear dispersion speed is 800–1000 rpm; in step S2, the ultrasonic dispersion time is 20–40 min; in step S3, the high-shear emulsification speed is 1200–1500 rpm, the high-speed homogenization speed is 2000–3000 rpm, the homogenization time is 2–5 min, and the system temperature is controlled at 18–20℃ during the preparation process.

9. The application of the honeycomb microporous in-situ phase-separated polymer ultraviolet liquid membrane according to any one of claims 1 to 6 in bird protection for building exterior walls, power transmission and distribution facilities, agricultural facilities, airport facilities and plant surfaces.

Citation Information

Patent Citations

  • Separation membrane modified by hydrophilic antifouling gel coating and preparation method thereof

    CN105833732A

  • Bird-impact-preventing optical flexible film and preparation method and application thereof

    CN114479693A

  • Particulate construct comprising polyhydroxyalkanoate and method for producing it

    EP1275378A2

  • Lipid particles on the basis of mixtures of liquid and solid lipids and method for producing same

    WO2000067728A2